ONE-PARAMETER PLANAR MOTION ON THE GALILEAN PLANE - Akar, Mutlu; Yuce, Salim; Kuruoglu, Nuri (INT ELECTRONIC JOURNAL GEOMETRY, 2013)
Muller [2], on the Euclidean plane E-2, introduced the one-parameter planar motions and obtained the relation between absolute, relative, sliding velocities and accelerations. Ergin [3] considered the Lorentzian plane L-2, instead of the Euclidean plane E-2, and introduced the one-parameter planar motions on the Lorentzian plane and also gave the relations between both the velocities and accelerations. In this paper, one-parameter motions on the Galilean plane G(2) are defined. Also the relations between absolute, relative, sliding velocities and accelerations and pole curves are discussed.
Keywords: Kinematics; one-parameter motion; Galilean plane; Mathematics